Expressive, communicative and cognitive levels color preference human as indicators to assess a person's psychological - S.-A. Y. Madyar; Y. E. Kovalevscaya; Y. V. Moiseyenko (Ukrainian Antarctic Journal, 2013)
Phenomena of mental and emotional state of a person caused by the impact of the expressive, communicative and cognitive factors of color, still leave many unsolved issues for research in the field of psychophysics, psychophysiology, and psychology. Answers to these questions would greatly facilitate the understanding of the process of psychological adaptation in an accelerated time world negative, destabilizing effect which violates psychophysical balance. This imbalance has a negative impact on the physical, emotional and intellectual state of man, especially in the extreme environment of stay. For the purpose of indepth disclosure mechanisms and patterns of psychophysical and psychophysiological reactions during human color perception conducted research involving Antarctic wintering. This choice is due to the peculiarities of their professional activities in a "color hunger" in monochromatic Antarctic environment. Research is based on the results of monitoring seasonal patterns perceptions locus combined with changes of psychological functions, giving the ability to define additional criteria for evaluating personal psychological qualities. Methods of assessing personality traits based on data obtained by determining color preference gives start developing new directions bioregulatory correction of psychophysiological status and more adaptive organism Antarctic winterers.